Manual extraction is superior to power tools when removing stripped titanium locking screws. Issue 11 (November 2021) - Nizaj, N.; Shamseer, C. Muhammed; Sukesh, A.N.; Varughese, Jacob; Theruvil, Bipin
Highlights: Removal of screws from locking plate is often difficult. This experimental study looks at two different methods of removal of seized screws. Extraction rate is better if done manually using T handle rather than using the extraction screw on power. Haptic feedback to engage the extraction screw on the damaged head is better with manual extraction. Abstract: Introduction: Removal of screws from a titanium locking plate is often difficult once the screw has seized and the head is damaged. Such stripped screws are removed with an extraction screw, which can be used manually or on power. We aim to compare the extraction rates using both these methods. Material and methods: We used 50, 3.5 mm diameter/20 mm long titanium locking screws. Fourth-generation saw bone models (radii) were used and 3.5 mm locking plates were fixed. The screws were deliberately over tightened and heads were damaged using a carbide drill to mimic stripped, seized screws. A left turn conical extraction screw coupled with a power tool was used for the first 25 screws and extraction screws coupled with a T handle for the remaining 25. A high-definition camera with a 60 fps frame rate was used to record the event. The time taken to remove screws from the plate was recorded. Results: When the extraction screw was used manually with T handle, we could remove 23 out of 25 screws (92%). When we used the extraction screw along with a power tool, 15 out of 25 (60%) locking screws were successfully removed. Conclusion: We recommend manual extraction with a T handle, rather than a power tool when removing the stripped locking screws (p-value <0.001). We feel that the haptic feedback provided when using manual extraction allows the surgeon to engage the extraction screws onto the damaged heads, thereby improving the extraction rates.